Enhance the productivity and nutrient use efficiency of greengram (Vigna radiata) through inorganic nutrients and biofertilizers - SINGH, R K; SINGH, S R K; TRIPATHI, UTTAM KUMAR; SRIVASTAV, VEENAPANI; RAI, H K (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was conducted at the Instructional Farm of Krishi Vigyan Kendra, Chhatarpur during two consecutive kharif of 2017-18 and 2018-19 to evaluate the effect of different biofertilizers along with 75 % recommended dose of fertilizers on growth, yield, nutrient uptake, nutrient use efficiency and B:C ratio of greengram (Vigna radiata L.). Results revealed that application of 75 % recommended dose of NPK along with seed treatment with Rhizobium @ 10 g/kg seed and soil application of PSB and KSB @ 5 kg/ha (T4) was found statistically at par with those obtained in T3 (recommended dose of NPK along with seed inoculation by Rhizobium and PSB separately @ 10 g/kg seed) and significantly superior over other treatments in terms of above parameters. Study also indicated that application of biofertilizers have potential to improve the productivity, with curtail the cost of production in terms of inorganic fertilizers and greater net returns and nutrient use efficiency.